Co-infection patterns of intestinal parasites in arboreal primates (proboscis monkeys, Nasalis larvatus) in Borneo. Issue 3 (December 2017) - Klaus, Annette; Zimmermann, Elke; Röper, Kathrin Monika; Radespiel, Ute; Nathan, Senthilvel; Goossens, Benoit; Strube, Christina
Abstract: Non-human primates of South-East Asia remain under-studied concerning parasite epidemiology and co-infection patterns. Simultaneously, efforts in conservation demand knowledge of parasite abundance and biodiversity in threatened species. The Endangered proboscis monkey, Nasalis larvatus, a primate flagship species for conservation in Borneo, was investigated in the present study. Habitat loss and fragmentation are among the greatest threats to bachelor and harem groups of this folivorous colobine. Designed as a follow-up study, prevalence and co-infection status of intestinal parasites from N. larvatus in a protected area in Malaysian Borneo were analyzed from fecal samples using a flotation method. For the first time, the intestinal parasite co-infection patterns were examined using quantitative analyses. Overall, 92.3% of fecal samples (N = 652) were positive for helminth eggs. Five helminth groups were detected: (1) trichurids (82.7% prevalence) including Trichuris spp. (82.1%) and Anatrichosoma spp. (1.4%), (2) strongyles (58.9%) including Trichostrongylus spp. (48.5%) and Oesophagostomum/Ternidens spp. (22.8%), (3) Strongyloides fuelleborni (32.7%), (4) Ascaris lumbricoides (8.6%), and (5) Enterobius spp. (5.5%). On average, an individual was co-infected with two different groups. Significant positive associations were found for co-infections of trichurids with strongyles and S. fuelleborni as well as S. fuelleborni with A. lumbricoides and strongyles. This study shows a high prevalence of various gastrointestinal helminths with potential transmission pathways primarily related to soil and with zoonotic relevance in wild proboscis monkeys in their remaining natural habitats. Observed positive associations of trichurids with strongyles and Strongyloides spp. may result from the high prevalence of trichurids. Similarly, positive associations between Strongyloides and Ascaris were found, both of which typically occur predominantly in juvenile hosts. These findings should be considered when proposing conservation actions in altered habitats nearby human settlements and when managing captive populations. Graphical abstract: Image 1 Highlights: First study on interactions of co-infecting helminthes in wild proboscis monkeys. 92% of fecal samples contain potentially zoonotic parasites. Five trichurid and three strongylid morphotypes significantly differ in size. Three reciprocal associations and one directed effect among five helminth orders. Juveniles may act as reservoirs for Strongyloides spp., Ascaris spp., and strongyles.